A hell of a storm : the battle for Kansas, the end of compromise, and the coming of the Civil War - Brown, David S. (David Scott), 1966- (Scribner, 2024)
"The history of the United States includes a series of sectional compromises--the Constitutional Convention, the Missouri Compromise in 1820, and the Compromise of 1850. While these accords created an imperfect republic, or "a house divided," as Lincoln put it, the country remained united. But then in 1854, this three-generations system suddenly blew up with the passage of the Kansas-Nebraska Act, and here, David Brown explores in riveting detail how the Act led to the sudden division of North and South. The Act declared that planters, if permitted by territorial laws, could bring their enslaved peoples to the land extending from the Mississippi River to the Rocky Mountains--the core of Jefferson's old Louisiana Purchase which had been reserved for free labor. Northerners were shocked that free soil might now be turned over to slavery and responded with unprecedented backlash. In the bill's wake the conservative Whig Party (winners of multiple presidential elections) collapsed, and the radical Republican Party was born--in six years it would take control of the central government, provoking Southern secession. In A Hell of a Storm, Brown brings history to life in a way that resonates with the events of present. Through chapters on Lincoln, Emerson, Stowe, Thoreau, and Tubman, along with a cast of presidents, poets, abolitionists, and black emigrationists, Brown weaves a political, cultural, and literary history that chronicles the Republican party's creation and rise, the collapse of antebellum compromises, and the coming of the Civil War, all topics that mirror current discussions about polarization in our nation today. By illuminating the personalities and the platforms, the writings and ideas that upended an older America and made space for its successor, A Hell of a Storm reminds us that American history is always being made, and it can be both dynamic and dangerous, both then and now"--